Integrating Network Pharmacology and Experimental Validation to Elucidate the Mechanism of Yiqi Yangyin Decoction in Suppressing Non-Small-Cell Lung Cancer. (20th February 2023) - Jiao, Pengfei; Wang, Yingrui; Ren, Gaofei; Chu, Dan; Li, Yameng; Sang, Tianqing
Abstract : Yiqi Yangyin Decoction (YYD) is a classic traditional Chinese medicine (TCM) formulation to treat lung cancer in clinic. Nevertheless, the active ingredients, key targets, and molecular mechanisms for YYD are still poorly understood. This study is focused on elucidating the pharmacological mechanism of YYD in non-small-cell lung cancer (NSCLC) by using a combined network pharmacology approach and biological experiment validation. Online bioinformatics tools showed that 40 bioactive compounds and 229 putative targets of YYD were associated with anti-NSCLC activity. Protein-Protein Interaction (PPI) network demonstrated AKT1, SRC, JUN, TP53, and EGFR as the top five key targets for YYD against NSCLC. Through enrichment analysis, YYD was found to affect cell proliferation and apoptosis in NSCLC possibly by PI3K-AKT signaling. Molecular docking confirmed a strong binding between the main compounds (quercetin or luteolin) and EGFR. As demonstrated by CCK-8, EdU, and colony formation assays, we found a significant inhibition of YYD on cell proliferation. Moreover, YYD treatment induced cell cycle arrest by affecting p53, p21, and cyclin D1 expression. YYD administration enhanced apoptosis by changing the expression of cleaved caspase-3, Bax, and Bcl-2. Mechanistically, YYD resulted in a significant inactivation of EGFR-PI3K-AKT signaling. Furthermore, EGFR activator significantly reversed YYD-mediated proliferation inhibition and apoptosis. YYD also showed an inhibitory effect on tumor growth in mice. Together, YYD might target the EGFR-PI3K-AKT pathway to repress NSCLC progression.